SOSIALISASI PEMASARAN PRODUK SECARA ON LINE PADA UMKM DI KELURAHAN KEBON AGUNG, KOTA SEMARANG - Manan, Abdul; Akriana NR, Fajar (Politeknik Indonusa Surakarta, 2023)
MSMEs business actors generally have limited knowledge of selling via online or social media. Therefore, the Community Service team intends to provide outreach about online media which can be used as an alternative in marketing the products of MSME business actors. The implementation method used in this service activity is to provide socialization about how people as consumers have moved to change their behavior in terms of meeting their needs, which initially visited many shopping places, but now they have started making purchases online. This is because it makes it easier for buyers, because they don't have to bother going to the sales point or shop. The number of internet users is increasing day by day. This has triggered the development of online transactions. Mentoring methods, interviews and discussions were carried out to help MSMEs business actors in carrying out efforts to enter online marketing for MSMEs business actors in Kebon Agung sub-district, East Semarang District, Semarang City.